2006
DOI: 10.1016/j.jlumin.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent properties of blue-emitting long afterglow phosphors Sr2−xCax MgSi2O7:Eu2+, Dy3+ (, 1)

Abstract: The luminescence of two newly developed blue-emitting long afterglow phosphors, Sr 2Àx Ca x MgSi 2 O 7 :Eu 2+ , Dy 3+ (x ¼ 0, 1), has been studied. The emission under VUV-UV excitation from a synchrotron radiation source, along with the long afterglow spectra have been measured at different temperatures ranging from 7 to 300 K. While the emission spectra under 170 nm excitation exhibit both the 5d-4f transitions of Eu 2+ and 4f-4f transitions of Dy 3+ , only the blue band corresponding to the 5d-4f transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…First, the actual photoionization of Eu 2+ to Eu 3+ is not at all clear and needs identification of the different Eu n+ species present in the material during UV-visible illumination (or during the trapping process) [16]. Up to now, the photoionization of Eu 2+ to Eu 3+ in Eu 2+ -containing phosphorescent material, Sr 2 MgSi 2 O 7 , has been observed by X-rays or VUV irradiation [16,17], but, as far as the present authors know, no direct experimental evidence has been advanced to support such photoionization behavior upon UV irradiation. Based on this, Hassinen et al [18] suggested that the creation of Eu 2+ -h + pairs upon UV irradiation was a more sophisticated choice.…”
Section: Introductionmentioning
confidence: 99%
“…First, the actual photoionization of Eu 2+ to Eu 3+ is not at all clear and needs identification of the different Eu n+ species present in the material during UV-visible illumination (or during the trapping process) [16]. Up to now, the photoionization of Eu 2+ to Eu 3+ in Eu 2+ -containing phosphorescent material, Sr 2 MgSi 2 O 7 , has been observed by X-rays or VUV irradiation [16,17], but, as far as the present authors know, no direct experimental evidence has been advanced to support such photoionization behavior upon UV irradiation. Based on this, Hassinen et al [18] suggested that the creation of Eu 2+ -h + pairs upon UV irradiation was a more sophisticated choice.…”
Section: Introductionmentioning
confidence: 99%
“…The typical spectrum of Eu 2+ ions is attributed to transition from the excited state 4f 6 5d to the ground state 4f 7 [4][5][6]. The emission spectra of yellow and blue luminescent fiber are similar with SrAl 2 O 4 : Eu 2+ , Dy 3+ .…”
Section: Spectrum Analysismentioning
confidence: 78%
“…However, it is water soluble. Sr 2 MgSi 2 O 7 : Eu 2+ , Dy 3+ , a water-insoluble afterglow material, was recently proposed by numerous research groups [15][16][17][18]. If these afterglow materials can be nanosized, they would be very useful in many fields.…”
Section: Introductionmentioning
confidence: 99%